2015
DOI: 10.3390/polym7071269
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Release of Insulin from Layer-by-Layer-Deposited Polyelectrolyte Microcapsules

Abstract: Insulin-containing microcapsules were prepared by a layer-by-layer (LbL) deposition of poly(allylamine hydrochloride) (PAH) and polyanions, such as poly(styrenesulfonate) (PSS), poly(vinyl sulfate) (PVS), and dextran sulfate (DS) on insulin-containing calcium carbonate (CaCO3) microparticles. The CaCO3 core was dissolved in diluted HCl solution to obtain insulin-containing hollow microcapsules. The microcapsules were characterized by scanning electron microscope (SEM) and atomic force microscope (AFM) images a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…In contrast, spheres prepared with the LbL‐assembled (κCF/PAA) n were ruptured after dissolution in the HF solution. Figure b shows the flattened balloon‐shaped hollow microcapsules presenting the successful preparation of hollow microcapsules . The AFM plane images presented in Figure b indicate the overwrapped thickness of 49.6 nm for two (κCF/PSS) 6.5 shells.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, spheres prepared with the LbL‐assembled (κCF/PAA) n were ruptured after dissolution in the HF solution. Figure b shows the flattened balloon‐shaped hollow microcapsules presenting the successful preparation of hollow microcapsules . The AFM plane images presented in Figure b indicate the overwrapped thickness of 49.6 nm for two (κCF/PSS) 6.5 shells.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are examples of doxorubicin (DOX) drug delivery systems being pH dependent. (Seib et al 2013;Zou et al 2017;Yoshida et al 2015). However the stepwise release after lowering the pH value results from unique properties of DOX itself and cannot be applied to other cytostatic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, its better solubility in acidic solutions was expected. The gradual insulin release from microcapsules prepared by a layer-bylayer deposition of poly(allylamine hydrochloride) and polyanions, such as poly(styrene sulfonate), poly(vinyl sulfate), and dextran sulfate was tested by Yoshida et al (2015) The authors observed a faster release in basic environment than in acidic solutions and explained the phenomena by a different charge density of poly(allylamine hydrochloride) which is unstable in solutions of higher pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, LbL assembly on NPs surface incorporating drug has not been extensively studied. In other LbL-based techniques, NPs are coated with PE and subsequently, the core is sacrificed to create a hollow core inside which drugs are loaded to form drug -loaded NPs 26 . The loading capacity of the drug in hollowed out NPs with LbL coating is controlled by the size of the core NPs.…”
Section: Earlier Inmentioning
confidence: 99%